Gene Expression Profile in Immortalized Human Periodontal Ligament Fibroblasts Through hTERT Ectopic Expression: Transcriptome and Bioinformatic Analysis - Nogueira, Lygia S.; Vasconcelos, Carolina P.; Mitre, Geovanni Pereira; Bittencourt, Leonardo Oliveira; Plaça, Jessica Rodrigues; Kataoka, Maria Sueli da Silva; Pinheiro, João de Jesus Viana; Garlet, Gustavo Pompermaier; De Oliveira, Edivaldo H. C.; Lima, Rafael R. (Frontiers in Molecular Biosciences, 2021)
Human periodontal ligament fibroblasts cells (hPLF) play an important role in maintaining oral cavity homeostasis with especial function on tissue regeneration and teeth maintenance in alveolus. Although their primary cell cultures are considered a good experimental model with no genetic changes, the finite lifespan may limit some experimental design. The immortalization process increases cell lifespan but may cause genetic changes and chromosomal instability, resulting in direct effects on physiological cell responses. In this way, we aimed to investigate the global gene expression hPLF after the immortalization process by the ectopic expression of the catalytic subunit of the enzyme reverse transcriptase or telomerase (hTERT) through transcriptome analysis. The primary culture of hPLF and immortalized (hPLF-hTERT) also had their embryonic origin tested by vimentin staining, hTERT synthesis evaluated through the indirect immunocytochemistry, analysis of cell proliferation and morphology. The results indicated hPLF and hPLF-hTERT positive for vimentin. On the 20th cell passage, hPLF was in senescence, while hPLF-hTERT maintained its proliferation and morphology characteristics. At the same passage, hPLF-hTERT presented a significant increase of the hTERT synthesis, but transcriptome did not reveal overexpression of the hTERT gene. Fifty-eight genes had their expression altered (11 up-regulate and 47 down-regulated) with the absence of changes in the key genes related to these cell type and in the main cancer-associated genes. In addition, the increase of hTERT protein expression without the overexpression of its gene indicates post-transcriptional level regulation. Successful immortalization of the hPLF through the ectopic expression of hTERT encourage further studies to design experimental protocols to investigate clinic questionings based on a translational perspective.